PENGARUH PERSISTENSI LABA TIMELINESS LAPORAN KEUANGAN DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP EARNING RESPONSE COEFFICIENT - Komang Gunawan; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2021)
The return response coefficient is a measure of the securities market return scale that responds to the portion of unexpected returns reported by the securities issuing company. Information on earnings is the thing most responded to by investors because it provides an overview of the company's performance. This study aims to determine the continuity of earnings, the timeliness of financial reporting, and the effect of corporate social responsibility on the earnings response coefficient. This research was conducted at Manufacturing Companies Listed on the IDX for the 2016-2018 Period. The sample in this study were 59 manufacturing companies during 2016-2018. The data testing used classical hypothesis testing, multiple linear regression analysis, hypothesis testing and the coefficient of determination. The results showed that the income persistence variable had a positive and significant effect on the income response coefficient. Financial report timeliness had a positive and significant effect on the earning response coefficient. While the corporate social responsibility variable has a negative and significant effect on the earning response coefficient.